Inflammatory microenvironment of fibrotic liver promotes hepatocellular carcinoma growth, metastasis and sorafenib resistance through STAT3 activation. Issue 3 (7th January 2021) - Jiang, Yuchuan; Chen, Peng; Hu, Kaishun; Dai, Guanqi; Li, Jinying; Zheng, Dandan; Yuan, Hui; He, Lu; Xie, Penghui; Tu, Mengxian; Peng, Shuang; Qu, Chen; et al.
Abstract: The pro‐inflammatory and pro‐fibrotic liver microenvironment facilitates hepatocarcinogenesis. However, the effects and mechanisms by which the hepatic fibroinflammatory microenvironment modulates intrahepatic hepatocellular carcinoma (HCC) progression and its response to systematic therapy remain largely unexplored. We established a syngeneic orthotopic HCC mouse model with a series of persistent liver injury induced by CCl4 gavage, which mimic the dynamic effect of hepatic pathology microenvironment on intrahepatic HCC growth and metastasis. Non‐invasive bioluminescence imaging was applied to follow tumour progression over time. The effect of the liver microenvironment modulated by hepatic injury on sorafenib resistance was investigated in vivo and in vitro. We found that the persistent liver injury facilitated HCC growth and metastasis, which was positively correlated with the degree of liver inflammation rather than the extent of liver fibrosis. The inflammatory cytokines in liver tissue were clearly increased after liver injury. The two indicated cytokines, tumour necrosis factor‐α (TNF‐α) and interleukin‐6 (IL‐6), both promoted intrahepatic HCC progression via STAT3 activation. In addition, the hepatic inflammatory microenvironment contributed to sorafenib resistance through the anti‐apoptotic protein mediated by STAT3, and STAT3 inhibitor S3I‐201 significantly improved sorafenib efficacy impaired by liver inflammation. Clinically, the increased inflammation of liver tissues was accompanied with the up‐regulated STAT3 activation in HCC. Above all, we concluded that the hepatic inflammatory microenvironment promotes intrahepatic HCC growth, metastasis and sorafenib resistance through activation of STAT3.